Identity comfort as the primary driver of TikTok acceptance small business owners - Pamungkas, Indra Novianto Adibayu; Ali, Dini Salmiyah Fitrah; Dananjaya, I Kadek Arya (Bricolage : Jurnal Magister Ilmu Komunikasi, 2026)
This study investigated how Tiktok adoption functions as a process of self-concept among small-business owners. This research focused on communication identity as the elementary stage, suggesting that social media usage does not constitute a full digital transformation; rather, it is the integration of digital platforms into small-business owners’ identities. This research constructed the Communication Theory of Identity (CTI) and the Technology Acceptance Model (TAM) to explain the subjective internalization of objective technological functions. This research applied a qualitative approach with NVivo 12 Pro analysis of 11 small-business owners in Bali. The study determined a new phrasing, “Socio-Technical Syncretizes," to show small-business owners who harmonize personal values with platform affordances. Findings revealed that “identity comfort” was a more significant driver of perceived usefulness than technical ease of use. By establishing identity alignment as a critical antecedent to technology acceptance, this research offered a novel theoretical synthesis that explained why some practitioners achieve digital sustainability while others resist. These results suggested that genuine digital inclusion required support systems that address the psychological and identity-based dimensions of technology, far from beyond simply technical training.